International conference “’Between the Carrot and the Stick’: Emerging Needsand Forms for Non-State Actors including NGOs and Informal Organizationsin Contemporary Russia” - Marina Spirina (Journal of Economic Sociology, 2016)
The international conference “‘Between the Carrot and the Stick’: Emerging Needs and Forms for Non-State Actors including NGOs and Informal Organizations in Contemporary Russia” was held at the Aleksanteri Institute, University of Helsinki, on January 28–29, 2016. The conference was organized by the Centre for Independent Social Research (St. Petersburg, Russia) in collaboration with the Aleksanteri Institute, University of Helsinki (Helsinki, Finland), Uppsala University (Uppsala, Sweden), and the Norwegian Institute for Urban and Regional Studies (Oslo, Norway). The organizing committee comprised Linda Cook (Brown University, USA), Ann-Mari Sätre (Uppsala University, Sweden), Elena Bogdanova (Centre for Independent Social Research, Russia), Meri Kulmala (Aleksanteri Institute, University of Helsinki, Finland), Aadne Aasland (Norwegian Institute for Urban and Regional Studies, Norway), and Eleanor Bindman (Queen Mary College, University of London, United Kingdom).The conference was dedicated to the problems of non-profit organizations in Russia in the context of the transformation of the political and legal conditions. The conference consisted of six sections, covering such topics as the transformation of the institutional conditions of the NGO sector in Russia, Russian NGOs in an international dimension, and new types of NGO emerging in the changing organizational environment. There were 24 papers presented during the conference by researchers from 10 countries. In addition, a round table was organized with participants from Russian and Finnish NGOs and researchers, during which issues of cooperation between social scientists and representatives of NGOs was discussed.Over 70 people attended the conference. The working language of the conference was English.